Glomerular filtration rate and cardiometabolic risk in an outpatient pediatric population with high prevalence of obesity. (15th October 2013) - Di Bonito, Procolo; Sanguigno, Eduardo; Forziato, Claudia; Di Fraia, Teresa; Moio, Nicola; Cavuto, Luigi; Sibilio, Gerolamo; Iardino, Maria Rosaria; Di Carluccio, Carla; Capaldo, Brunella
<x xml:space="preserve">Abstract</x> Objective To evaluate the relationship between estimated glomerular filtration rate (eGFR) and cardiometabolic risk factors (CMRF) in an outpatient pediatric population with high prevalence of obesity. Design and Methods eGFR was evaluated in 901 children unselected for chronic kidney disease of whom 694 were overweight/obese (6‐16 years) and 207 were age‐ and sex‐matched normal weight (NW). We generated three categories of eGFR: mild‐low eGFR (< 20th percentile), high eGFR (>80th percentile) and intermediate eGFR (20‐80th percentile), considered as the reference category Results Children with either mild‐low or high eGFR category showed a 2‐4 fold higher Odds ratio of high blood pressure, left ventricular hypertrophy, and microalbuminuria compared with children of the intermediate eGFR category. In addition, children with mild‐low eGFR levels showed a 1.5‐2 fold higher Odds ratio of impaired fasting glucose and high white blood cell count compared with children with intermediate eGFR levels. Conclusions In outpatient children with high prevalence of obesity, children with either mildly reduced or high eGFR have an increased burden of CMRF. Children with eGFR < 97 mL/min/1.73 m2 show a worse CMR profile. This finding supports the usefulness to assess eGFR to identify children with unfavorable CMR profile.